Intervention in the Supreme Court of Canada's Bissonnette case: Assessing the relationship between international and Canadian criminal law - Vincent-Wright, Sarah-Michèle; Cohen, Miriam; Beaulac, Stéphane (Lex Electronica)

(untitled) (Centre de recherche en droit public Université de Montréal, 2024)
This article, which follows the authors' intervention in the Bissonnette case before the Supreme Court of Canada, highlights the jurisprudential context surrounding the analytical framework upon which judges are called to base their interpretation and application of Canadian domestic law - in this case, the sentencing regime under sections 7 and 12 of the Canadian Charter - when resorting to the normativity of international law. In addition to clarifying the persuasive value of international criminal law norms in the interpretation of the Canadian Charter, this paper seeks to nuance the principles of sentencing review under international criminal law, which differ from those under Canadian domestic law. Essentially, this consolidation of existing interlegal principles serves to correct the ambiguity left by the Quebec Court of Appeal, which, had it not been for the Supreme Court decision, could have led to the instability and unpredictability of the case law on the application of international law in Canadian law.